Group of girls on a bridge in the forest - Unknown:::Creator::::::::::::
Negative shows a group of girls on a bridge spanning a dry gully in a forest. Below the bridge is a man and what appear to be two other people. They are probably at the YWCA's Camp Ayun Mapu in Big Basin, California.